Single Trans apical access for double aortic and mitral valves-in-valves procedures with high risk of thrombus embolism - Adjedj, Julien; Kirsch, Mathias; Nowacka, Anna; Muller, Olivier (Journal of Cardiology and Cardiovascular Medicine, 2019)
Persistent left atrial thrombus remains a contra indication to transeptal valves in valves procedure. We aimed to perform a double valves in valves replacement through transapical access with cerebral angiography control during the procedure just after implantation. Our case shows the feasibility of this strategy and the management of right ventricle laceration successfully treated after extra corporeal membrane oxygenation implantation and local hemostasis. We reported a feasibility case report of successful double valves in valves implantation through transapical access with 6 months of clinical and computed tomography follow up.